EVALUATION OF THE HEATING SYSTEM FROM AN INJECTION MOLDING MACHINE - LUMINITA BIBIRE; NARCIS BARSAN (Journal of Engineering Studies and Research)
Injection is an economical process characterised through an increased productivity that leads, in the majority of cases, to finite pieces. The process of injection includes two distinctive phases, firstly, when the melting occurs, followed by the homogenisation and the creation of pressure; the process takes place in the plasticizing unity; coming next being the second phase that consists in the forming of the producs, in the cavity of the matrix. Regarding the main factors, the purpose of this paper was insuring a thermic regime as uniform as possible in order to obtain an appropriate plastifying process. To do this, with the help of a thermovision camera type Fluke Ti20, the thermic regime has been studied in the area of the plastifying cylinder, following the balancing of the heating resistances.